FACTORS ASSOCIATED WITH NUTRITIONAL STATUS OF CHILDREN UNDER FIVE YEARS OF AGE IN GUNUNGSITOLI IDANOI PRIMARY HEALTHCARE CENTER - Novrin Senselia Putri Ziliwu; Lina Dewi Anggraeni; Rosa Nora Lina (Universitas Airlangga, 2020)
The number of children under five years of age suffering from underweight was 28.0% in Gunungsitoli district. Out of six primary Healthcare centers in the district, Gunungsitoli Idanoi Primary Healthcare Center Healthcarewas one of the six primary healthcare centers with the highest malnutrition prevalence. Sixty-four children under five years of age there Healthcaresuffered from malnutrition. This study aimed to identify factors associated with the nutritional status of children under five in Gunungsitoli Idanoi Primary Healthcare Center, Gunungsitoli district. It was an analytical survey with a cross-sectional approach conducted in Gunungsitoli Idanoi Primary Healthcare Center in February 2019. Data were collected using a questionnaire. This study had samples as many as 246 mothers of children under five years of age selected using a purposive random sampling technique. The bivariate analysis indicates the nutritional status of children under five was significantly associated with mother’s employment status (p=0.043) and family size (p=0.015). While the nutritional status of children under five had no significant association with mother’s knowledge of nutrition (p=0.485), mother’s education (p=0.616), family income (p=0.511), infectious disease (p=0.913), and history of breastfeeding (p=0.847). Mother’s employment status and family size affected the nutritional status of children under five. The primary Healthcare center should cooperate with stakeholders across sectors, especially conduct training for improving economic business skills of the people in the village, and promote family planning program for couples of childbearing age. Keywords: Breastfeeding, children under five years of age, underweight, mother’s knowledge, mother’s employment.